Young masters vs. elite swimmers: comparison of performance, energetics, kinematics and efficiency - Mejias, J.E. (2015)
Competition in masters swimming is getting tougher. Athletes are dedicating more time and effort to excel in masters competitions than they use to. Research question: What are the factors associated with masters and elite swimmers performance? Type of study: A cohort group comparison (young master versus elite swimmers) and a correlational study (association between selected variables and performance) were conducted. Purpose: The aim was to identify the energetics, kinematics and efficiency variables associated with young masters (former elite) and elite swimmers performance as well as compare it between both cohort groups. Methods: Twenty male swimmers (masters: N=8, 29.75±3.80-y; elite: N=12, 20.41±3.20-yld) performed a 7x200m freestyle swim. The performance (200m freestyle at official competition), velocity at which the 4 mmol.l-1 of blood lactate was assessed (V4), peak blood lactate concentrations (Lapeak), peak oxygen up-take (VO2peak), minimum velocity to elicited VO2peak (vVO2peak), total energy expenditure (Ėtot), stroke frequency (SF), stroke length (SL), mean swimming velocity (v), energy cost (C), stroke index (SI) and propelling efficiency (p) to check whether this was achieved. Results: Elite swimmers presented a better performance. V4, VO2peak, vVO2peak, Ėtot , SF, v and SI were significantly higher in elite swimmers. For both groups performance was associated with the V4, vVO2peak and v. In addition, elite swimmers’ performance was impaired with regard to the Lapeak. Conclusions: Young masters swimmers presented impairment in performance related to a decrease in the energetics profile and biomechanical behaviour. Nevertheless, their previous background as elite swimmers allowed them to maintain high swimming efficiency.